Factors Affecting Return on Asset at Himbara Bank in Indonesia - Nanda Destiliansi; Eka Dewi Anggraini (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research aims to analyze the influence of Net Interest Margin (NIM), Operating Expenses, Operating Income (BOPO), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR) on Return On Assets at State-Owned Association Banks (HIMBARA) in Indonesia. This type of research uses secondary data based on 2010-2022 panel data. Data were analyzed using panel data regression using the Eviews analysis tool. The research results show that Net Interest Margin (NIM) has a significant effect on Return On Assets (ROA). Operational Income (BOPO) has a significant effect on Return On Assets. Loan to Deposit Ratio (LDR) has no effect on Return On Assets. Meanwhile, Non-Performing Loans (NPL) do not have a significant effect on Return On Assets at Bank Himbara in Indonesia.